Digital-Based Consumer Behavior in Support Green Economy - Erwansyah, Erwansyah (Journal of Community Research and Service, 2023)
As technology advances, people™s preferences for shopping in digital formats will change. Cashless payment systems such as GoPay, OVO, and ShopeePay are increasingly popular among consumers, so Bank Indonesia has issued a new policy to encourage their use. This research was conducted with the aim of knowing the influence of digital-based consumer behavior. This study uses primary data with a sample of application users with GoPay, OVO and ShopeePay respondents in Medan. The data processing method used in this research is using the method of Structural Equation Modeling (SEM). Using SEM can help researchers to assess the nature of measurements and test theoretical relationships (1). The results of this study indicate that there are six hypotheses that have positive results, namely innovativeness, optimism about perceived usefulness. Innovativeness and optimism have a positive effect on perceived ease of use. The results of this study also show that perceived usefulness and perceived ease of use have a positive influence on behavioral intention. While there are four variables in this study rejected, namely insecurity and discomfort have no effect on perceived usefulness. Likewise, insecurity and discomfort have no effect on perceived ease of use.